PENGARUH ENTREPRENEURIAL ORIENTATION DAN INTERACTIVITY TERHADAP BUSINESS PERFORMANCE MELALUI INNOVATION CAPABILITY PADA UMKM WOMENPRENEURS DI SIDOARJO - Irsyadia, Latifah; Novie, Muhafidhah; Muzdalifah, Laily; Kamila, Edita Rachma (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Entrepreneurial Orientation (EO) and Interactivity (IN) on Business Performance (BP) with Innovation Capability (IC) as a mediator in MSME womenpreneurs in Sidoarjo. The research method uses a quantitative approach with data obtained through a questionnaire from 209 respondents, then analyzed using SmartPLS. The results showed that Interactivity has a significant positive effect on Business Performance both directly and through Innovation Capability, while Entrepreneurial Orientation did not show a significant effect through the mediation of Innovation Capability. These findings indicate the importance of Interactivity in driving innovation that improves business performance. However, Entrepreneurial Orientation needs to be optimized to support innovation in womenpreneurs. This research recommends innovation training programs and strengthening access to technology to help womenpreneurs overcome innovation obstacles, so as to increase the competitiveness and contribution of MSMEs to the local economy.